ANALYSIS OF WATER QUALITY STATUS USING METHOD OF WATER POLLUTION INDEX: A CASE STUDY ON THE DENDENG RIVER - Suwari (International Journal of Research -GRANTHAALAYAH, 2021)
The Dendeng River is vital for economic sustainability and viability for the community, industry and commerce around the flood plain of the river as well as raw water sources of the Kupang PDAM. However, increased domestic and industrial waste disposal along the river has caused severe pollution. One way to maintain the quality of the river is by continuously monitoring the pollutants and applying technology control as well as controlling strategy. The aim of the research mainly is to establish the water quality status of Dendeng River by water pollution Index method based on parameter physics and chemistry, i.e. pH, DO, COD, BOD, TSS, TDS, NH3-N, NO2-N, NO3-N, and PO4-P. The research was carried out based on field survey and sample examined in situ and in laboratory. The removal of water sample from Dendeng River conducted based on composite sampling as many as six point locations of Dendeng River as representative of upstream up to downstream zone. The quality status of Dendeng River is in good condition to lightly polluted with a pollution index value of 0.6 to 1.52. Value of the DO, BOD, COD, and phosphate content were higher than the allowable class 1 standard. The Water Quality Index value of Dendeng River was 86.67, which is included in the good water quality class.